Interferon gamma receptor expression on granulocytes of cardiac surgical patients is modulated differently by the type of cardiopulmonary bypass used - Jankovicova, K; Kolackova, M; Kunes, P; Holubcova, Z; Krejsek, J; Mandak, J (Perfusion, 2012)
AIMS: To follow the IFNγ receptor expression on monocytes and granulocytes of cardiac surgical patients with respect to the type of cardiopulmonary bypass (CPB). METHODS: Expression of IFNγ receptor on monocytes and granulocytes of 26 cardiac surgical patients operated with the use of either "standard" or "miniaturised" CPB was determined by flow cytometry. RESULTS: The significant increase in IFNγ receptor expression on monocytes on the 1(st) and on the 3(rd) postoperative days was revealed in both groups of patients (p<0.001) irrespective of the type of CPB used, being non-significantly different between groups. In contrast, the expression of IFNγ on granulocytes displayed significant differences in terms of the CPB used. Whereas, in "standard" CPB patients, granulocyte INFγ receptor expression reached its maximum immediately after surgery (p<0.01), in "miniivasive" CPB patients, the peak in INFγ receptor expression was postponed to the 1(st) postoperative day (p<0.05). Statistically significantly higher IFNγ receptor expression on granulocytes was found in "standard" CPB patients (p<0.05). CONCLUSION: Compared to "miniaturised" CPB patients, the significantly higher IFNγ receptor expression on granulocytes was found in "standard" CPB patients (p<0.05) on the 1(st) postoperative day.
Keywords: kardiochirurgické výkony; miniaturizace; Humans; lidé středního věku; Postoperative Period; Aged; Cardiopulmonary Bypass; Interferon gamma Receptor; senioři; lidé; receptory interferonů; Cardiac Surgical Procedures; kardiopulmonální bypass; granulocyty; Male; Flow Cytometry; Middle Aged; Monocytes; průtoková cytometrie; monocyty; Miniaturization; mužské pohlaví; pooperační období; receptor interferonu gama; Receptors, Interferon; Granulocytes